Examining the Importance of Intentionally Structuring the Youth Sport Context to Facilitate Positive Youth Development. Issue 4 (1st October 2016) - Bean, Corliss; Forneris, Tanya
Abstract : Researchers argue that sport must be deliberately structured to teach life skills. The purpose of this study was to examine differences in program quality and positive developmental outcomes across 3 youth programming contexts (intentional sport, nonintentional sport, intentional leadership) pertaining to the importance of intentionally teaching life skills. Researchers conducted 184 observations, and 377 youth completed 2 questionnaires. Results indicated intentionally structured programs scored higher on program quality and positive youth development outcomes than nonintentionally structured programs, with intentional sport scoring significantly higher on some measures of program quality and positive youth development than leadership programs. Practical implications and future research areas are discussed.